Kegiatan Keagamaan Majelis Ta’lim Dalam Penanggulangan Dampak Covid-19 - Desy Naelasari (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2023)
The purpose of this research is to describe the disease of COVID-19 in Jepara district and to explain how the implementation of the study by Tafsir Amaly manages the stress of the community in Tigajuru Village and Welahan Village of Jepara District. The research methods used in this research are qualitative research methods and quantitative descriptive design techniques. Data collection in this study is done in three ways: interview, observation and documentation. Research results: (1) The impact of COVID-19 in Jepara district: a. The effect of economic change: income is decreasing and cannot work. b. The impact of psychological change: anxiety and stress (stress). (2) Implementation of the Amaly Tafsir Study in dealing with the stress of the community in Tigajuru and Welahan villages: (a) Planning: The research activities of Amaly Denagn pay attention to the time and methods or studies that will be used. (b) The implementation: (1) Tigajuro village: using general methods to interpret Amaly in general. (2) Welahan village: Special methods (Tababbur methods): understand, live, and think about every word and every verse of the Qur'an. (c) Evaluation: (1) The condition of the citizens who became more calm and more enthusiastic to do daily activities after the appointment of the Amaly Tafsir study (2) The request of citizens to be appointed to an amaly tafsir study once a week.